2022
DOI: 10.3390/s22031250
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality, Serious Games and Picture Exchange Communication System for People with ASD: Systematic Literature Review and Future Directions

Abstract: For people with Autism Spectrum Disorder (ASD), using technological tools, such as augmented reality (AR) and serious games remain a new and unexplored option. To attract people with ASD who have communicative, social, emotional and attention deficit disorders to behavioral treatments, an attractive environment is needed that ensures continuity during treatment. The aim of the current work is to efficiently examine systematic reviews and relevant primary studies on ASD solutions from 2015 to 2020, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 108 publications
(80 reference statements)
0
26
0
1
Order By: Relevance
“…It also generates an increase in motivation, the development of research capacity and skills for communication and problem-solving. From the above research studies (Almurashi et al, 2022;Aggarwal and Singhal, 2019;Hsiao et al, 2012;Khan et al, 2019;L opez-Faic an and Ja en-Mart ınez, 2020), it can also be concluded that AR in education enables the understanding of complex spatial relationships and abstract concepts along with self-learning. Finally, AR in education facilitates learning by doing.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…It also generates an increase in motivation, the development of research capacity and skills for communication and problem-solving. From the above research studies (Almurashi et al, 2022;Aggarwal and Singhal, 2019;Hsiao et al, 2012;Khan et al, 2019;L opez-Faic an and Ja en-Mart ınez, 2020), it can also be concluded that AR in education enables the understanding of complex spatial relationships and abstract concepts along with self-learning. Finally, AR in education facilitates learning by doing.…”
Section: Introductionmentioning
confidence: 89%
“…The study of the characteristics of AR leads us to consider the advantages that its use in education can generate. In this line, there are several studies (Almurashi et al. , 2022; Aggarwal and Singhal, 2019; Hsiao et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, the use of VR as a treatment modality has grown. Of note, there are recent studies examining the effectiveness of AR/VR-based therapeutic modalities in the management of patients with neurodevelopmental spectrum conditions (such as autism spectrum disorders, attention deficit hyperactivity disorders) [ 20 , 21 , 22 , 23 ], anxiety disorders (such as phobias) [ 24 , 25 , 26 , 27 ], obsessive compulsive disorder [ 28 , 29 , 30 ], post-traumatic stress disorder [ 31 ], and cognitive impairments in the elderly [ 32 , 33 ]. In comparison, there are fewer studies specifically elucidating the effectiveness of AR/VR based interventions as a psychoeducational tool such as in improving understanding of mental illnesses, engendering more positive attitudes regarding people with mental illnesses [ 34 , 35 ] and reduction of stigma [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%